Calculus and analytic geometry - Thomas, George B. (George Brinton) Jr. 1914-2006; Finney, Ross L. (Addison-Wesley Publishing Company, 1996)
The ninth edition of this college-level calculus textbook features end-of-chapter review questions, practice exercises, and applications and examples.